2008
DOI: 10.1016/j.ajog.2008.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Memy I: a novel murine model for uterine leiomyoma using adenovirus-enhanced human fibroid explants in severe combined immune deficiency mice

Abstract: OBJECTIVE-This study was undertaken to develop a representative murine model for human leiomyoma.STUDY DESIGN-Human fibroid tumor tissues were cut into small pieces and treated with medium alone, adenoviral-β-galactosidase, adenoviral-vascular endothelial growth factor-A, adenoviral-cyclooxygenase-2, or both adenoviral-vascular endothelial growth factor-A and adenoviral-cyclooxygenase-2. Tissue pieces were inserted subcutaneously in the flank of each severe combined immunodeficient mouse. The developed lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 21 publications
1
37
0
1
Order By: Relevance
“…Using immunohistochemical studies, Gentry and colleagues found that vascular endothelial growth factor-A (VEGF-A) was overexpressed significantly in leiomyoma tissue as compared to the adjacent myometrium (103). It was demonstrated that VEGF is necessary for the growth of leiomyoma xenografts in vivo (104). VEGF represents a potential therapeutic target in leiomyoma, and Xu and colleagues demonstrated that it is downregulated by the selective progesterone receptor modulator CDB-2914 (105).…”
Section: Role Of Individual Growth Factors In Leiomyoma Pathobiologymentioning
confidence: 99%
“…Using immunohistochemical studies, Gentry and colleagues found that vascular endothelial growth factor-A (VEGF-A) was overexpressed significantly in leiomyoma tissue as compared to the adjacent myometrium (103). It was demonstrated that VEGF is necessary for the growth of leiomyoma xenografts in vivo (104). VEGF represents a potential therapeutic target in leiomyoma, and Xu and colleagues demonstrated that it is downregulated by the selective progesterone receptor modulator CDB-2914 (105).…”
Section: Role Of Individual Growth Factors In Leiomyoma Pathobiologymentioning
confidence: 99%
“…Nonetheless, the Tsc2-driven tumour development might not reflect the sporadic pathogenesis of myomas. An alternative model described by Hassan et al [41], who provoked growth of myoma-like xenograft implanted subcutaneously in SCID mice, by transplanting human tumour tissue pieces overexpressing COX2 (cyclooxygenase 2) and VEGF through adenoviral transduction. However, that model exhibits substantial limitations because it is driven by the ectopic overexpression of COX2 [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Ishikawa et al showed that the growth of tissue xenografts was strongly dependent on the cell density of the xenografts [22]. Hassan et al showed VEGF provoked growth of myoma-like xenografts implanted subcutaneously in SCID mice [41]. VEGFenhanced angiogenesis is also associated with an increase in vascular permeability, which results in an increase in the amount of growth factors and nutrients delivered to tumour cells [44,50].…”
Section: Discussionmentioning
confidence: 99%
“…Serum estrogen levels were maintained at high levels by subcutaneous implantation of 1.5 mg, 60-day sustained-release 17β -estradiol pellets (Innovative Research of America, Sarasota, FL, USA) as described previously (Hassan et al 2008). The pellets were implanted 2 days before the tissue transplantation.…”
Section: Animalsmentioning
confidence: 99%
“…Recently, to overcome such limitations, Memy I, a novel human uterine leiomyoma xenograft model, was developed. Human uterine xenografts pretreated with both adenoviral-cyclooxygenase-2 (COX-2) and adenoviral-vascular endothelial growth factor-A (VEGF-A) were implanted subcutaneously into severe combined immunodeficient (SCID) mice (Hassan et al 2008). In this model, human leiomyoma tissue could be engrafted and survive for at least 1 month.…”
mentioning
confidence: 99%